Masters of mystery : the strange friendship of Arthur Conan Doyle and Harry Houdini - Sandford, Christopher, 1956- (Palgrave Macmillan, 2011)
"Renowned mystery author Arthur Conan Doyle and famous illusionist Harry Houdini first met in 1920, during the magician's tour of England. At the time, Conan Doyle had given up his lucrative writing career, killing off Sherlock Holmes in the process, in order to concentrate on his increasingly manic interest in Spiritualism. Houdini, who regularly conducted seances in an attempt to reach his late mother, was also infatuated with the idea of what he called a "living afterlife," though his enthusiasm came to be tempered by his ability to expose fraudulent mediums, many of whom employed crude variations of his own well-known illusions. Using previously unpublished material on the murky relationship between Houdini and Conan Doyle, this sometimes macabre, sometimes comic tale tells the fascinating story of the relationship between two of the most loved figures of the 20th century and their pursuit of magic and lost loved ones"--